Individualism Values of Cowboy in the Film Open Range (2003) - ADZANI, RIFQI (LANTERN (Journal on English Language, Culture and Literature), 2017)
The presence of cowboy as the representation of the hero in the West is always substantial as they represent one of the values admired by Americans, individualism. Based on Wright’s theory about ‘natural’ individuals, individualism values represented by cowboy include rationality, autonomy, and self-interest. The existence of cowboy in Western is inseparable from elements familiarly portrayed, namely death, women and the language of men, landscape, horses, and cattle. The film Open Range (2003) illustrates two characters of cowboy named Boss and Charley, as they reflect the values in the way they think and behave in their life. Elements of Westerns in the film are illustrated as a means of supporting elements in the representation of individualism values of the cowboys.